2016
DOI: 10.1158/1078-0432.ccr-15-2035
|View full text |Cite
|
Sign up to set email alerts
|

Focusing on Core Patient-Reported Outcomes in Cancer Clinical Trials: Symptomatic Adverse Events, Physical Function, and Disease-Related Symptoms

Abstract: Cancer clinical trials have relied on overall survival and measures of tumor growth or reduction to assess the efficacy of a drug. However, benefits are often accompanied by significant symptomatic toxicities. The degree to which a therapy improves disease symptoms and introduces symptomatic toxicity affects how patients function in their daily lives. These concepts are important contributors to health-related quality of life (HRQOL). In this article, we discuss patient-reported outcome (PRO) assessment in can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
234
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(237 citation statements)
references
References 21 publications
1
234
0
2
Order By: Relevance
“…For this reason, the FDA and EMA assert that for assessment of symptoms or other domains that patients know best, PROs are the gold standard for data collection [1,8]. Collection of PROs with thoughtful implementation in clinical trials has been found to be feasible, with over 80% patient compliance in cooperative group trials and over 90% in many industry trials either with paper forms or electronic data collection via web, automated telephone system, or handheld device [9].…”
Section: Rationale For Using Pros In Drug Discoverymentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, the FDA and EMA assert that for assessment of symptoms or other domains that patients know best, PROs are the gold standard for data collection [1,8]. Collection of PROs with thoughtful implementation in clinical trials has been found to be feasible, with over 80% patient compliance in cooperative group trials and over 90% in many industry trials either with paper forms or electronic data collection via web, automated telephone system, or handheld device [9].…”
Section: Rationale For Using Pros In Drug Discoverymentioning
confidence: 99%
“…PRO questionnaires can also be used to support economic analyses such as costeffectiveness and may be requested or required by some authorities. PRO questionnaires are commonly used for this purpose and can also reflect overall impact on the health status or functioning of study participants, but may not have sufficient precision to reflect specific symptoms or aspects of physical functioning [8]. Treatment satisfaction can also be assessed as a supportive metric not for labeling purposes, for example as done in the evaluation of rivaroxaban for longterm anticoagulation in deep venous thrombosis [14].…”
Section: Uses Of Pros In Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 A focus on assessment and management of physical health and function is needed to promote improved health-related quality of life. 19,20 Recommendations and standards from the Institute of Medicine and the American College of Surgeons' Commission on Cancer, among others, provide a framework for alleviating deficits in cancer care and the resulting failures to recognize and manage functional loss and disability. [21][22][23] Rehabilitation professionals are an optimal addition to the cancer care team and offer expertise in functional assessment, morbidity management, and disability prevention.…”
mentioning
confidence: 99%
“…Kluetz et al from the FDA [1] provide a welcome overview of the challenges related to patient-reported outcomes assessment in cancer clinical trials seen from a regulatory perspective.…”
mentioning
confidence: 99%